Epistemic Decolonization as Overcoming the Hermeneutical Injustice of Eurocentrism - Posholi, Lerato (Philosophical Papers, 2020)
This paper is broadly concerned with the question of what epistemic decolonization might involve. It is divided into two parts. The first part begins by explaining the specifically epistemic problem to which calls for epistemic decolonization respond. I suggest that calls for decolonization are motivated by a perceived epistemic crisis consisting in the inadequacy of the dominant Eurocentric paradigm to properly theorize our modern world. I then discuss two general proposals, radical and moderate, for what epistemic decolonization might involve. In the second part, I argue that the inadequacy of Eurocentric epistemic resources constitutes a hermeneutical injustice caused by an irreducible form of epistemic oppression. I then argue that addressing this form of epistemic oppression requires thinking ‘outside’ of the Eurocentric paradigm because the paradigm might fail to reveal and address the epistemic oppression sustaining it. This lends further plausibility to the radical proposal that epistemic decolonization must involve thinking from ‘outside’ the Eurocentric paradigm, but also accommodates the moderate proposal that adopting critical perspectives on Eurocentric thought is an important part of epistemic decolonization.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; discours dominant; décolonisation épistémique; fem9000; féminisme décolonial; injustices herméneutiques; injustices épistémiques; philosophie; sciences humaines; système colonial; systèmes d'oppressions; thématiques; violences; études décoloniales

Se défendre : une philosophie de la violence - Dorlin, Elsa (Zones, 2017)
"En 1685, le Code noir défendait " aux esclaves de porter aucunes armes offensives ni de gros bâtons " sous peine de fouet. Au xixe siècle, en Algérie, l'État colonial français interdisait les armes aux indigènes, tout en accordant aux colons le droit de s'armer. Aujourd'hui, certaines vies comptent si peu que l'on peut tirer dans le dos d'un adolescent tout en prétendant qu'il était agressif, armé et menaçant. Une ligne de partage oppose historiquement les corps " dignes d'être défendus " et ceux qui, désarmés ou rendus indéfendables, sont laissés sans défense. Ce " désarmement " organisé des subalternes et des opprimés au profit d'une minorité jouissant d'un droit permanent à porter des armes et à en user impunément pose directement, pour tout élan de libération, la question du recours à la violence pour sa propre défense. Du jiu-jitsu des suffragettes aux pratiques insurrectionnelles du ghetto de Varsovie, des fusils des Black Panthers aux patrouilles queer, Elsa Dorlin retrace une généalogie philosophique de l'autodéfense politique. Derrière l'histoire officielle de la légitime défense, il est ici question du récit des " éthiques martiales de soi ", ces histoires ensevelies où le Sujet ne préexiste pas à sa propre défense, où le fait de se défendre en attaquant apparaît à la fois comme la condition de possibilité d'un soi et la matière des mythologies politiques. Cette histoire - une histoire de la violence - conditionne la définition même de la subjectivité moderne. Elle s'écrit à la lumière d'une relecture critique de l'histoire de la philosophie politique, où Hobbes et Locke sont à confronter avec Franz Fanon, Michel Foucault ou Judith Butler."--Page 1 et 4 de la couverture.
Keywords: afro-féminisme; approches et analyses; cours; discipline; fem3100; féminisme afroaméricain; féminisme décolonial; féminismes noirs; histoire et politique; mouvements sociaux; philosophie; premier cycle; racisme; sciences humaines; sexisme; systèmes d'oppressions; thématiques; violences

Towards a decolonial feminism - Lugones, Maria (Hypatia, 2010)
Dans « Heterosexualism and the Colonial/Modern Gender System » (Lugones 2007), j’ai proposé de lire la relation entre le colonisateur et le colonisé en termes de genre, de race et de sexualité. Je n’entendais pas par là ajouter une lecture genrée et une lecture raciale aux relations coloniales déjà comprises. J’ai plutôt proposé une relecture de la modernité coloniale capitaliste moderne elle-même. C’est parce que l’imposition coloniale du genre traverse les questions d’écologie, d’économie, de gouvernement, de relations avec le monde des esprits et de connaissance, ainsi que les pratiques quotidiennes qui nous habituent à prendre soin du monde ou à le détruire. Je propose ce cadre non pas comme une abstraction de l’expérience vécue, mais comme une lentille qui nous permet de voir ce qui est caché de notre compréhension de la race et du genre et de la relation de chacun avec l’hétérosexualité normative.
Keywords: amériques; approches et analyses; colonialité du genre; corps; discipline; féminisme décolonial; histoire et politique; hétérosexisme; philosophie; philosophie politique; racisme; régions géographiques; sciences humaines; sexualité; système colonial; systèmes d'oppressions; thématiques; violences

Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." -- Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles